Creating Team Competency for Idea Generation and Implementation of Energy Efficient Innovation in Buildings - Intrachooto, Singh; Lin, Tina; Chu, Caroline; Hsu, Jovan (Journal of Architectural/Planning Research and Studies (JARS), 2002)
This paper reports the initial findings of an ongoing study that aims to identify the mechanisms that foster technical innovation in the building industry, specifically energy efficient innovations. Building practice is a complex and collective endeavor, which involves a large number of different parties (knowledge experts, manufacturers, and suppliers), specialized design, and a variety of types of contracts. These collaborative efforts, however, do not necessarily produce a technologically innovative building due to other forces such as economics, preferences, and constructability. Nonetheless, it is clear that some buildings are more innovative while others maintain the traditional conventions. The investigation finds that team competency or ‘relational competence’ of team members to achieve Energy Efficient Innovation (EEI) in buildings depends largely on the commitment of project participants and their collaborative climate, which, in turn, is a function of five interrelated factors: Green alliance and criteria formulation; value-based relationship; feedback cycle; green driver and leadership; and the prospect of future collaboration.